Phatic meanings of key words in popular science journalism - Prokofeva, Natalia A. (Neophilology, 2020)
The purpose of the research is to demonstrate the functioning of key words in the texts of popular science journalism. Modern media text is created not only to inform, but to attract the reader. This enlarges the role of contact-building means, for example – the address to the epoch key words. We consider the peculiarities of phatic meanings in popular science journalism, dedicated to the historic themes. The research contains the analysis of phatic meanings in two randomly chosen issues of historic magazines. The result of the analysis is the selection of two groups of key words, which make the journalistic text contain additional phatic meanings. The first group of words is the current key words, allowing relating the publication, containing the address to a historical event or a historical person, to the actual reality. This lexical group allows the journalist to make the publication politically critical and topical and also to evaluate the current political situation through the historical parallel. Such word usage allows including ironic subtext in the historical journalism. The second group of words is the key words of a single publication; they allow completely characterizing an event or a person, being in the center of a journalist’s attention. These are the words, which relate to the acute for the Russian culture value meanings. They stay aside with the complete semantics and characterize the speech subject, the journalist’s relation to it, but they do not relate the theme to the current political situation.